A Comprehensive Review on Evolving Landscape of Drug Therapies for Diabetes - Roni Weinberg Sibony; Omri Segev; Saar Dor; Itamar Raz (Medical Research and Its Applications Vol. 4, 2024)
The last decade has seen the advent of new medications for lowering blood glucose levels. These medications also exhibit a remarkable capacity to alleviate cardiovascular risk factors. This comprehensive review highlights the evolving landscape of pharmacotherapy in diabetes, the drugs currently available for treating diabetes, their effectiveness and efficacy, the impact on target organs, and side effects. This review also provides an overview of oral and injectable non-insulin medications used to improve blood glucose levels. This work also provides insights that can support the customization of treatment strategies. We delve into the concept of precision medicine and explore the role of older drugs in patient management. Furthermore, we present a proposal for a groundbreaking approach to the treatment of type 2 diabetes, with an emphasis on striving for a cure for the disease. The treatment of type 2 diabetes (T2D) necessitates a multifaceted approach that combines behavioral and pharmacological interventions to mitigate complications and sustain a high quality of life. Treatment encompasses the management of glucose levels, weight, cardiovascular risk factors, comorbidities, and associated complications through medication and lifestyle adjustments. Metformin, a standard in diabetes management, continues to serve as the primary, first-line oral treatment across all age groups due to its efficacy, versatility in combination therapy, and cost-effectiveness. Glucagon-like peptide-1 receptor agonists (GLP-1 RA) offer notable benefits for HbA1c and weight reduction, with significant cardiovascular benefits. Sodium-glucose cotransporter inhibitors (SGLT-2i) lower glucose levels independently of insulin while conferring notable benefits for cardiovascular, renal, and heart-failure outcomes. Combined therapies emphasizing early and sustained glycemic control are promising options for diabetes management. As insulin therapy remains pivotal, metformin and non-insulin agents such as GLP-1 RA and SGLT-2i offer compelling options. Notably, exciting novel treatments like the dual GLP-1/ glucose-dependent insulinotropic polypeptide (GIP) agonist show promise for substantially reducing glycated hemoglobin and body weight. Recent studies have highlighted a clear correlation between reducing HbA1c to less than 6.5% and a significant decrease in microvascular and macrovascular complications. Studies also suggest the potential benefits of primary combined therapy for glycemic management in diabetes compared to monotherapy with metformin across a wide range of baseline HbA1c levels. The most effective way to manage diabetes is to treat it with a combination therapy from the time of initial diagnosis. To help medical staff choose the ideal drug combination for each patient, the National Diabetes Council in Israel developed a calculator that recommends the most appropriate combination therapy based on the patient’s BMI, HbA1c levels, and risk for ischemic heart disease, stroke, renal function, and heart failure. Along with the most appropriate drug treatment, a healthy lifestyle is extremely important.